The Effect of Isometric Exercise on Self Care Ability in Stroke Infarction Patients in Garut Regency - Zahara Farhan; Devi Ratnasari; Dani Sujana; Milani Nazi’ah; Azis Gandri Mabarti (Jurnal Penelitian Pendidikan IPA, 2025)
Stroke infarction is caused by blockage in the cerebral artery blood vessels which results in disorders in the limbs so that isometric exercise is needed to increase the patient's muscle strength in meeting their basic needs. The purpose of this study was to determine the effect of isometric exercise on self-care ability in stroke infarction patients in Garut Regency. Quasi-experimental design with one group pre-test and post-test design with a sample size of 15 stroke infarction patients who had undergone treatment at the hospital. The sampling technique used consecutive sampling. Data collection used SOP from Technol Health care and the DSCAI-90 instrument. Data analysis used Paired t-test. This study was conducted from October to November 2024 in the Wanaraja Health Center working area, Garut Regency. The results of the Paired t-test, the average self-care ability pre-post isometric exercise action was 18.667 and a p value of 0.00 was obtained. One of the ultimate goals of isometric exercise is to improve the patient's ability to meet self-care needs and individual well-being so that the patient's ability to perform self-care agency increases. There is an effect of isometric exercise on self-care ability in stroke infarction patients. The results of the study can be used in the development of health promotion programs for health centers in carrying out follow-up care for stroke infarction patients at home.